Central Park West : a crime novel [large type] - Comey, James B., Jr., 1960- (Thorndike Press large print mystery series., 2023)
"When a years-long case against a powerful mobster finally cracks and an unimpeachable witness takes the stand, federal prosecutor Nora Carleton is looking forward to putting the defendant away for good. The mobster, though, has other plans. As the witness's testimony concludes, a note is passed to the prosecution offering up information into the assassination of a disgraced former New York governor, murdered in his penthouse apartment just days before. It's enough to blow the case wide open, and to send Nora into a high-stakes investigation of conspiracy, corruption, and danger"--